Starting from scratch: Developing and sustaining a rural research team lessons from a nutrition and dietetics case study. (20th October 2021) - Brown, Leanne J.; Urquhart, Lisa; Squires, Kelly; Crowley, Elesa; Heaney, Susan; Kocanda, Lucy; Schumacher, Tracy
Abstract: Objective: To describe the development of and key factors for sustaining a rural‐based research team focussed on nutrition and dietetics. Design: A longitudinal embedded case study approach with data sourced from publicly available records and observations. Case study sub‐units were developed into 3 phases with analysis using theoretical propositions and pattern matching. Quantitative data were descriptively analysed. Setting: University of Newcastle Department of Rural Health across 4 rural sites. Participants: Publicly available data sources from existing team members. Main outcome measures: Staffing levels, research supervision, internal and external grant outcomes and peer‐reviewed journal publications. Result: Academic staffing has increased by 4 full‐time equivalent positions over 18 years, with 6 current higher‐degree research students. Key factors identified in the development of a discipline‐specific research workforce included staff higher degree by research completions, longevity of staff in research‐active roles, immersive rural placements with a research component and collaborations with nationally competitive researchers. Rural pilot research projects, community connections, understanding of the local context and research networks were fundamental to establishing a viable team. Conclusion: Systematically investing in research that is embedded in local communities will ensure sustainability and relevance, capacity building of existing staff and an ability to problem solve at the local level. Sustained and focussed investment is needed if the current rural research workforce is to develop towards a capacity that meets current demand.